2021
DOI: 10.1007/s40120-021-00289-6
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Residual Excessive Daytime Sleepiness Due to Obstructive Sleep Apnea: Insights for Optimizing Patient Outcomes

Abstract: Although excessive daytime sleepiness (EDS) attributable to obstructive sleep apnea (OSA) can be resolved by consistent usage of and effective treatment (often with the use of continuous positive airway pressure therapy), 12–58% of patients report residual EDS (REDS). While REDS is difficult to treat, a proportion of cases are possibly due to reversible issues, and wake-promoting medications can prove useful for the remaining cases. Given the challenges associated with effective management of REDS and its rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 101 publications
(146 reference statements)
1
3
0
2
Order By: Relevance
“…Residual sleepiness is associated with a constellation of multidimensional symptoms (eg, fatigue, depression), altering quality of life and the patient's overall perception of good health. 7,20 In the current study, significant and sustained improvements were also demonstrated for a vigilance test (OsLer) and for functional status (fatigue, quality of life, and the physician's global assessment scales).…”
Section: Discussionsupporting
confidence: 56%
“…Residual sleepiness is associated with a constellation of multidimensional symptoms (eg, fatigue, depression), altering quality of life and the patient's overall perception of good health. 7,20 In the current study, significant and sustained improvements were also demonstrated for a vigilance test (OsLer) and for functional status (fatigue, quality of life, and the physician's global assessment scales).…”
Section: Discussionsupporting
confidence: 56%
“…Mounting evidence demonstrates that sleep disorders are becoming prevalent health issues worldwide, with an estimate of 150 million people suffering from them ( 9 ). OSA is one of the most detected sleep disorders causing excessive daytime sleepiness along with other potential sleep disorders ( 10 ). Yet, about 80% of moderate and severe OSA cases remain undiagnosed ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The morphologically detectable changes are partially reversible by successful PAP therapy 66 121 122 123 . The irreversible morphologic brain changes are associated with residual daytime sleepiness despite adequate therapy 64 78 124 .…”
Section: Obstructive Sleep Apnea Syndrome and Cognitionmentioning
confidence: 99%
“…Die morphologisch nachweisbaren Veränderungen sind teilweise durch eine erfolgreiche PAP-Therapie reversibel 66 121 122 123 . Die irreversiblen morphologischen Hirnveränderungen werden mit einer residuellen Tagesschläfrigkeit trotz ausreichender Therapie in Verbindung gebracht 64 78 124 .…”
Section: 41 Pap-therapieunclassified